Embryo Culture of Lycopersicon esculentum × L. peruvianum Hybrid Genotypes Possessing Heat-stable Resistance to Meloidogyne incognita - Cap, Guillermo Bartolome (1991)
Genotypes of Lycopersicon peruvianum (L.) Mill. and L. peruvianum var. glandulosum (Rick), selected from accessions that possess resistance to Meloidogyne incognita [(Kofoid and White) Chitwood] at high soil temperature (30C), were used as male parents in crosses with L. esculentum (Mill.) susceptible cultivars UC82, Lukullus, Tropic, and male-sterile line ms-31, respectively. The incongruity barrier between the two plant species was overcome by embryo callus and embryo cloning techniques. Hybridity of the F, progeny obtained from each cross was confirmed by differences in leaf and flower morphology, plant growth habits, and by acid phosphatase isozyme phenotypes using polyacrylamide gel electrophoresis. In greenhouse inoculation experiments, F1 plants were highly resistant to M. incognita in soil at 25 and 30C. These results confirmed the successful transfer and expression of heat-stable resistance to M. incognita from L. peruvianum to hybrids with L. esculentum as a preliminary step to introgressing additional root-knot nematode resistance into tomato.